Clinical spectrum and outcome of nocardiosis in Oman: a case series from a single center - Deodhar, Divya; Hassan, Kowthar Salman; Rawahi, Ghada N. Al (International Journal of Research in Medical Sciences, 2025)
Nocardiosis is an opportunistic bacterial infection caused by aerobic Gram-positive bacteria belonging to the actinomycetes group. With the increase in the population of immunocompromised patients, these infections have been identified in the middle east countries. In a retrospective study of 13 years, we found ten patients who were culture confirmed nocardiosis. Among this series, pulmonary nocardiosis predominated with 80%. Most of the species of Nocardia were identified using the molecular testing, 16S rRNA gene sequencing and drug susceptibilities were performed in 70% and 60% respectively. Treatment is usually based on susceptibility testing which give a better clinical cure and outcome. Cotrimoxazole formed the back bone of the treatment. Although, small in number, this case series is the largest reported from the any middle east country and it can assist the clinicians with high clinical suspicion of infection and early treatment.